Determinants of agricultural land price in Poland – a case study covering a part of the Euroregion Baltic - Kocur-Bera Katarzyna (Cahiers Agricultures, 2016)
The main aim of this study was to identify the factors that drive the prices of agricultural property after Poland's accession to EU in regions where agriculture is the predominant mode of production. A statistical model of real estate prices was developed based on the conducted transactions. The key determinants of agricultural property prices were: location of land relative to rural settlements, soil quality, land fragmentation, forest cover in the municipality and location of farms in less-favored areas with natural handicaps for agricultural production. The last attribute results from Poland's membership in the European Union and participation in the Common Agricultural Policy. The support scheme increased the prices of agricultural property. Our results are largely consistent with the findings of international studies. They provide valuable inputs for prospective buyers of agricultural property and investors.